Requirements for Implementing Integrated Procurement of Floating Units for Nedaja Overseas Mission - Reza Roshani; Alireza Bayati; Mohhamad Hadi Hashemzade (علوم و فنون نظامی, 2023)
With the advancement of technology, the concept of logistics underwent extensive changes. Traditional logistics, no longer met the needs of customers, so it moved towards the integration of functions and processes. As the Navy's area of responsibility expanded, the duration of the naval mission also increased, but there was no change in the way floating units were supported. One of the major problems of traditional logistics is the time it takes to prepare floating units for deployment abroad. . The present study, which has been compiled in a descriptive method and with a mixed approach, has been conducted in order to explain the requirements for the implementation of an integrated procurement system in navy overseas missions. The statistical population includes 145 all logistics experts who have served in the floating unit and have at least a bachelor's degree and 20 years of service. . Interviews, questionnaires and library studies were used as data collection tools. . The results showed that in order to integrate the procurement of floating units, must be removed and principles of integrated logistics must be observed in all its components, which are: Reforming the organizational structure of logistics from a task to process orientation, elimination of duplicate components and activities, convergence of goals by strategic management levels, effective interaction between all components, comprehensive database, understanding the limitations of other components, perfect coordination between the flow of information and materials along the logistics chain, all information available in different parts of the organization have a specific format.